Sosialisasi Olahraga Hockey pada MGMP KKG PJOK di Kota Mataram - Primayanti, Intan; Nachamory Oemar, Fitry; Jamaludin; Kusuma, Lalu Sapta Wijaya; Subakti (Program Studi Pendidikan Jasmani, Universitas Samudra, 2025)
Hockey is a relatively new sport developing in West Nusa Tenggara Province, with promising achievements demonstrated by the NTB team’s participation in the 2023 National Sports Week (PON). To support the development of hockey and the training of young athletes, a socialization program was conducted targeting physical education teachers (PJOK) of junior and senior high schools in Mataram City. The program aimed to disseminate hockey rules and technical aspects so that teachers could effectively become facilitators in athlete development at schools. The socialization was carried out through workshops and field practice over two days at the Mataram City Sports Arena, involving PJOK teachers from various schools. Evaluation was conducted using observation and questionnaires to measure improvements in participants’ knowledge and skills. The results showed a significant increase in understanding and enthusiasm during hockey practice sessions. This activity contributes to enhancing PJOK teachers’ competencies and supports hockey development in Mataram City, fostering the emergence of potential athletes capable of achieving provincial and national level achievements. Further recommendations include ongoing mentoring and provision of adequate training facilities to ensure sustainable hockey development in the region.